Isolation and characterisation of insulin-releasing compounds from Crotalus adamanteus, Crotalus vegrandis and Bitis nasicornis venom. (July 2015) - Moore, Sara W.M.; Bhat, Vikas K.; Flatt, Peter R.; Gault, Victor A.; McClean, Stephen
Abstract: Crude venom from three venomous snakes, Crotalus adamanteus, Crotalus vegrandis and Bitis nasicornis was fractionated by gel filtration chromatography, and selected fractions screened for in-vitro insulinotropic activity using clonal pancreatic BRIN-BD11 cells. Nineteen fractions stimulated insulin secretion and the structural identity of bioactive compounds responsible was probed using MALDI-ToF MS and N-terminal Edman degradation sequencing. Partial N-terminal sequences were determined and their homology to existing sequences identified using BLAST searching. The main insulinotropic peptide families identified were made up of snake venom serine proteinases, phospholipases A2 (PLA2 ) and disintegrins. Snake venom constituents may have therapeutic potential for diabetes, with each of the three viper venoms tested providing insulinotropic compounds from a range of different toxin families. Highlights: Crotalus adamanteus, Crotalus vegrandis and Bitis nasicornis venoms have insulinotropic effects. Fractions screened for in-vitro insulinotropic activity in clonal pancreatic BRIN-BD11 cells. Active fractions investigated by N-terminal sequencing and BLAST searching. Venom components stimulating insulin secretion include proteinases, PLA2s and disintegrins.